Upaya Mendukung Global Goals Melalui Pelatihan Budidaya Maggot Sebagai Alternatif Pakan Ikan Pada Kelompok Wanita Econatural di Kota Makassar - Kaslam Kaslam; Nur Azizah Lutfiah Budiman; Ema Anggriani; Farah Adiba (Jurnal Abdimas Adpi Sosial dan Humaniora, 2022)
The global goals proclaimed by world leaders contain three main problems to be solved, namely poverty, inequality and the environment which are translated into 17 sustainable development goals. These seventeen programs can only be realized if people at the local level can actively participate in utilizing their potential. One small step at the local level that can be implemented is a training program on maggot cultivation as an alternative to fish feed by involving women. Maggot which is the larvae of the BSF fly has many benefits for both the economic sector and the environment. There are at least four global goals programs that are very relevant to this community service activity, namely eradicating poverty, reducing hunger, gender equality and responsible consumption and production. Maggot cultivation can be an alternative business activity for the community which is very profitable. Maggot as a quality feed for livestock indirectly contributes to food production so that it can inhibit the rate of hunger in the community. Not only men, women can also be involved in this activity, so that gender equality can be realized. In addition, maggot is also a responsible link in the production and consumption process because it is in line with environmental sustainability, namely breaking down waste to produce various kinds of organic products. Thus, maggot cultivation can be a productive alternative for the community.